Wykluczenie nierozerwalności małżeństwa (kan. 1101 § 1 KPK) w świetle wyroku Roty Rzymskiej c. Serrano Ruiz z 27 maja 2005 r. - Góralski, Wojciech (Ius Matrimoniale, 2014)
The judgment (pro nullitate matrimonii) was issued in the third instance (it was negative in the first instance and positive in the second instance) due to the exclusion of marriage indissolubility by the woman, which was married to the man for 10 years; three children were born during the marriage. On the basis of testimonies of the parties and witnesses, as well as taking into consideration all circumstances, however, Roma Rota judges had no doubt that the petitioner excluded marriage indissolubility by her positive act of will, permeated with divorce ideas during her stay in Great Britain and persuaded to the marriage by her father (not in the meaning of can. 1103 CIC).